2020
DOI: 10.56093/ijas.v90i6.104765
|View full text |Cite
|
Sign up to set email alerts
|

Study on quality parameters of grapes (Vitis vinifera) and raisins affected by grape type

Abstract: Grape (Vitis vinifera L.) is one of the most important fruit crops of the country well known for health benefits. Varietal variations are recorded in quality of grapes and processed products. In present study 10 grape varieties (white seedless and colour seeded) were evaluated for properties of grapes and raisins. Bigger bunches were recorded in H-27 and closely followed by Manjari Naveen while maximum weight of 10 berries was observed in E8-5. Among these higher TSS was recorded in Manjari Kishmish (22.40°B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…to more number of canes or immaturity of canes in different varieties. Similar line of work in grapes was reported by Havinal (2007) [10] and Somkuwar et al, (2020) [35] . [37] .…”
Section: Yield Parameterssupporting
confidence: 84%
“…to more number of canes or immaturity of canes in different varieties. Similar line of work in grapes was reported by Havinal (2007) [10] and Somkuwar et al, (2020) [35] . [37] .…”
Section: Yield Parameterssupporting
confidence: 84%
“…The data recorded on yield attributing parameters are presented in the [20] and [21], yield is mainly correlated to the number of grape clusters, but also the traits of grape clusters and berries, as well as the number of grape berries per cluster [22] reported that Red Globe vines grafted on Dogridge followed by Salt Creek rootstock recorded higher yield per vine. [23] found that both the inherent vigour of the scion that conferred by the rootstock were contributing factors to yield performance.…”
Section: Yield Parametersmentioning
confidence: 99%
“…The higher temperature in the tropics may lead to an increase in sugar content and a decrease in acids. Somkuwar et al (2020) revealed that the grape types affect raisin quality as every grape type has its features like berry size, Titrable Acidity (TA), total soluble solids, etc. and it reflects in the quality of the dried grapes.…”
Section: Varietymentioning
confidence: 99%
“…As the organoleptic score is related to the quality of grapes and drying conditions so variability is recorded. Somkuwar et al, (2020) also recorded variability in the organoleptic quality of raisins produced from different varieties.…”
Section: Organoleptic Testmentioning
confidence: 99%
See 1 more Smart Citation